Associations between Household Food Insecurity and Depressive Symptomology among Adolescent Girls and Young Women during the COVID-19 Pandemic in South Africa - Stanley Carries; Lovemore Nyasha Sigwadhi; Audrey Moyo; Colleen Wagner; Catherine Mathews; Darshini Govindasamy (MDPI AG, 2024)
Evidence suggests an association between food insecurity and depressive symptomatology; however, little is known about the association between adolescent girls and young women (AGYW) in the context of COVID-19. This study aimed to investigate the relationship between household food insecurity (HFI) and depressive symptomology among AGYW in South Africa during the COVID-19 pandemic. Secondary data analysis was conducted using cross-sectional data collected from the HERStory2 study conducted during the COVID-19 pandemic. The data were collected from 515 AGYW (aged 15-24 years) recruited from six South African districts using a demographic detail and socio-economic questionnaire as well as the Center for Epidemiological Studies Depression (CESD-10) Scale. Data were fitted using a multi-variable robust Poisson regression model and controlled for sociodemographic and health factors. The results suggest that the majority of the sample of AGYW were 20 years old, with 74% exposed to HFI and 30.29% experiencing depressive symptomology. AGYW exposed to HFI were 1.80 times at risk of depressive symptomology compared to those from food-secure households [adjusted risk ratio (aRR): 1.80; 95% CI: 1.35-2.42, p < 0.0001)]. Future pandemic-preparedness strategies should incorporate screening for HFI as a means to identify AGYW who may require psychosocial support.